Avaliação das células de Leydig das regiões periférica e intermediária do parênquima testicular de suínos: marcadores moleculares, eficiência esteroidogênica e proporção de macrófagos - Luiza Alves Andrade Colen (2020)
Two morphologically distinct Leydig cells types are recognized within the interstitial compartment of pigs testes. Moreover, these cells seem to present a preferential distribution, since the hypertrophied cell type is observed in the intermediate region (ID), and those cells with small individual volume are more frequent in the peripheral region of testis parenchyma. Therefore, the present study aimed to phenotypically characterize these two cell populations, in order to better understand the functional differences they may present. In this regard, in testes from postpubertal pigs, we observed that Leydig cells in RP presented a weak intensity of ERα labeling, whereas the proliferation index found for this population was higher. No differences regarding AR and LHR immunoreactivity were observed. Additionally, we evaluated the steroidogenic function in ID and RP through the xenografting approach that enabled to assess in vivo the synthesis of androgens. Indeed, ID presented a clear trend and the recipient showed high levels of testosterone. On the other hand, macrophages were more observed in RP. These findings suggest that Leydig cells in RP are mainly progenitors and immature types, whereas ID maintain the mature type. However, further studies are being developed so to better comprehend the cells’ interactions and how they modulate the different regions of testis parenchyma.